VENDOR MANAGED INVENTORY WITH CONSIGNMENT FOR DETERIORATING ITEMS IN THREE ECHELONSUPPLY CHAIN - FITRA - Nim: 23415052 , DESMY
In this research, VMI-C in three echelons (i.e. one supplier, one vendor, and one retailer) is investigated. We analyzed the effect of deteriorating item on the total cost in each echelon and the total cost of supply chain system. We developed a mathematical model to determine the optimal number of replenishments and the lot-size of replenishments that minimize the total cost. We analyzed the sensitivity of the demand, the deterioration rate, and the holding cost rate with respect to the total cost. We found that VMI-C with deteriorating item results in more cost at the downstream levels. Most of the cost comes from product deterioration in the warehouse. The demand rate and the production rate greatly affect the total cost for each player. The trend is generally increasing. The increasing deterioration rate also affected the total cost of the supply chain. The holding cost has a positive effect to change the total cost.